DIGITAL FINANCIAL LITERACY, FINANCIAL STRESS, AND SCAM AWARENESS: THE MODERATING ROLE OF FINANCIAL BEHAVIOR - Kevin Widjanarko; Christopher Bradley Budiono; Evelyn Evelyn (Jurnal Terapan Ilmu Manajemen dan Bisnis, 2025)
Investment scams are everywhere. So we need to understand better what makes people notice financial risks online. The purpose of this study is to analyze the influence of Digital Financial Literacy (DFL) and Financial Stress (FS) on Awareness of Investment Scam (AoIS) in Indonesian young adults, moderated by Financial Behavior (FB). Based on the Theory of Planned Behavior (TPB) and the Stress and Coping Theory, this study explains how digital financial knowledge, financial stress, and financial behavior interact in forming awareness of digital investment scam. The research uses a quantitative associative method and involves 400 respondents aged 20–40 years who actively use social media. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results of the measurement model show good reliability and validity. The structural model shows that DFL, FS, and FB have a significant effect on AoIS. In addition, FB strengthens the influence of DFL on AoIS and reduces the influence of FS on AoIS. The findings show that higher digital financial literacy and good financial behavior increase people’s awareness of investment scams, while financial stress that is managed adaptively can also increase alertness through a problem-focused coping process.